KAJIAN POLA DISTRIBUSI PANGAN (BERAS, BAWANG PUTIH, KACANG TANAH, KACANG MERAH, KACANG HIJAU) DI KOTA KUPANG - Melgiana S. Medah; Chris N. Namah (Politeknik Pertanian Negeri Kupang, 2018)
Distribution is the activity of moving products from sources to consumers using distribution channels at the right time (Assauri, 2004). A distribution channel is a structure reflecting alternative channels and various ventures (such as producers, wholesalers, and retailers). The objectives of this study are (1) Identification of patterns of food distribution (rice, garlic, groundnuts, kidney beans, mung beans) in Kupang city; (2) Identification of food supplier areas in the city of Kupang. This research is a set ofsurvey activities, and the data collected is sourced from primary and secondary data. The methods used in this study are descriptive method and the sampling technic which is taken from 100 traders in the city of Kupang which are situated in 4 main traditional markets (Oesapa, Oeba, Inpres, and Oebobo). The results showed that rice agents held 75 percent of the distribution patterns with the distribution system of rice as such: agents - distributors - retailers - consumers. Whereas 25 percent are local rice with distribution patterns, farmers - collectors - consumers. Regarding the garlic distribution, 100 percent held by garlic agents supplying directly to retailers before reaching consumers. Unlike garlic, peanut and mung beans distribution patterns are 90 percent held by collectors, and directly sold to consumers, and only 10 percent goes consumers through retailers.Kidney beans commodities 70 percent goes to traders - 10 percent goes to retailers - consumers. Sulawesi and Surabaya are the two main rice suppliers for the region make up 75 percent. Surabaya also funnels 100 percent imported garlic from China to Kupang. While groundnuts and kidney beans are provided 80 percent by TTS farmers, 15 percent Ende farmers and 5 percent from Surabaya. About mung beans, 70 percent are coming from Malaka district, 30 percent from Camplong, Oeso and Semau. Except for red beans which are sometimes supplied from Surabaya around 10 percent, the other types of beans are most of the times always available in NTT.